Analysis of Spectroscopic, Morphological Characterization and Interaction of Dye Molecules for the Surface Modification of TiB2 Nanoparticles. (15th October 2022) - Mayakannan, S.; Rathinam, R.; Saminathan, Rajasekaran; Deepalakshmi, R.; Gopal, Mahesh; Hillary, J. Justin Maria; Nanthakumar, S.; Ganvir, V. Y.; Singh, Pallavi
Abstract : Nanoparticles of titanium diboride (TiB2 ) coated with a conductive polymer and subjected to an oxidizing agent was carried out in this research. TiB2 nanoparticles coated with polypyrrole (PPy) were studied using XRD and TEM techniques. Nitrogen adsorption and desorption properties of nanoparticles are covered with modified polypyrrole to understand better the surface zone, structural features, and pore geometries of the nanoparticles. The water-based hazardous anionic Congo red (CR) dye was removed using polypyrrole-coated titanium diboride (PPy@TiB2 ) nanoparticles. Numerous cutting-edge experimental techniques, including FTIR, FE-SEM, EDXS, and element mapping analysis, were used to confirm the CR color's adhesion to the PPy@TiB2 nanoadsorbent study. While conducting batch experiments, coated TiB2 nanoadsorbents with polypyrrole enhanced the adsorption behaviour. One of the factors evaluated in the adsorption tests was pH; another was contact time, and a third was dose. At pH = 4, 98.75% of Congo red dye was detached using 60 mg of PPy-coated TiB2 nanoadsorbent. Several sorption-desorption cycles were performed on this nanoadsorbent to determine its reusability. An excellent adsorption capacity for water treatment is reported in PPy-coated TiB2 nanoadsorbent.